Navigating Challenges and Innovations in Emergency Online Teaching: A Qualitative Inquiry - Abdullah Azzam Tuzgen; Yao Yang; Alissa Cress (COVID)
The COVID-19 pandemic disrupted U.S. K-12 education systems, forcing teachers to adopt emergency remote teaching with minimal preparation. This study investigates the challenges and adaptive strategies of 16 U.S. K-12 educators during the pandemic. Qualitative analysis of semi-structured interviews with 16 educators was conducted to identify key themes. Findings reveal that innovative engagement strategies—including interactive activities, long-term projects, and inclusive virtual environments—were pivotal for sustaining participation. Challenges such as disparities in students’ home environments, technical limitations, and motivational declines underscored the need for parental collaboration, emotional support frameworks, and teacher-specific professional development. These results highlight actionable pathways to strengthen resilience and equity in online education systems during crises.